VCAM-1, ICAM-1 and selectins in gestational diabetes mellitus and the risk for vascular disorders - Siddiqui, Khalid; George, Teena P; Nawaz, Shaik Sarfaraz; Joy, Salini Scaria (Future cardiology, 2019)
Levels of VCAM-1, ICAM-1 and selectins in gestational diabetes mellitus (GDM) subjects are an indication of endothelial dysfunction predicting the future metabolic consequence via metabolic memory effect. This cross-sectional study was conducted in 92 pregnant women and serum endothelial cell adhesion molecules were measured using Randox biochip analyzer. Significantly elevated serum level of VCAM-1 was found in GDM subjects and in greater than equal to one parity categorized GDM group when compared with control. The correlation of parity and P-selectin was statistically significant in GDM subjects. Elevated levels of endothelial cell adhesion molecules in GDM women indicate an imbalance in vascular function. Transient hyperglycemia during pregnancy may induce persistent modifications to the memory cells and GDM subjects are more prone to develop future consequences.